Roosting habits of disk-winged bats, especially Thyroptera discifera - Pine, Ronald H.; Gomez Zamora, Gianfranco; Reid, Fiona A.; Timm, Robert M. (THERYA, 2023)
Roosting habits of disk-winged bats of the genus Thyroptera (Chiroptera: Thyropteridae) have been unknown to very poorly known except for those of the commonly encountered T. tricolor. Many secondary literature publications state that roosting habits of Thyroptera in general are those of tricolor, known to roost almost exclusively in vertical, unfurling large leaves, especially of native Heliconia and introduced banana (genus Musa). However, so far as known, no other species of Thyroptera chooses such roosts. Until 1993, the only species of Thyroptera known were tricolor and discifera—they had been the only two known for 139 years. During this long period, the unique roosting habits of tricolor often were attributed to the genus as a whole, as sometimes still happens today. Now there are three more known species—lavali, devivoi, and wynneae. In this paper, we correct misconceptions concerning roosting habits in Thyroptera, summarize what is known for all five species, and provide the first detailed observations on roosting in discifera. Thyroptera discifera has been found roosting attached to the underside of a palm leaflet or leaflets in Brazil and in conically curled portions of dead banana leaves in Costa Rica.